The Effect of Bioethanol and Pertamax Mixtures on Exhaust Gas Emissions from a 4-Stroke Engine in Motorcycle Matic - Listiyono Listiyono; Muhammad Afif Bahrain; Eko Yudiyanto (Widyagama University of Malang, 2022)
Bioethanol is an alternative fuel to substitute fossil oil. Bioethanol has several advantages in its use as a fuel in addition to its renewable nature, and bioethanol is also believed to reduce some motor vehicle emissions. The purpose and objective of this study were to determine the effect of a mixture of Bioethanol and Pertamax on gas emissions in a 4-stroke motor with variations in the fuel mixture and engine cycle. This test method is carried out with the measurement parameters of CO, HC, CO2, and O2. Tests on motor vehicles were carried out with variations of BP0 (0% Bioethanol) to BP100 (100% Bioethanol). The test results using a gas analyzer and analyzed using excel show that bioethanol cannot reduce exhaust gas emissions. Adding bioethanol fuel to Pertamax can also increase the fuel's octane number (RON) and specific gravity. From the available data, adding bioethanol can reduce HC emission levels by up to 4ppm at BP50 at 6000 rpm, increasing CO2 emissions by 13.4% at BP50 at 7000 rpm with a compression ratio of 13:1. For the lowest O2 emission level, it reaches 0.13%. at BP40 at 5000 rpm. CO emission levels are still relatively small in various mixtures with a yield of 0.01%, but at BP0 and BP80 at 13:1 compression, emissions tend to increase every rpm.